Voices of Today, Leaders of Tomorrow: Implications of Female Undergraduate Students' Involvement in Clubs and Associations - Low, Kah Choon; Senasi, Vally; Mohamad, Siti Syuhadah; Mokthsim, Noranida (2021)
In this ever-challenging world, every organization requires workers with new skills in the economy. In order to employed and sustained the employees, the employers need the best breed of students to enter the labour market. Do students' involvement in clubs and associations equipped them with the best attributes that are needed in the job market? Based on past studies, there were limited studies conducted on the voices of female students and their developments in joining clubs and associations in the university. Therefore, this study aims to investigate the benefits of joining students' clubs and associations in shaping the female students' development in their undergraduate years. Focus group discussions were conducted in three phases with 24 female respondents to determine the students' involvement in clubs and associations and the impacts on their career developments. Three thematic categories of data emerged from the study, focusing on students' involvement in programs, challenges in conducting programs and future program recommendations. The present study has implications for the university's policies and budgets, student affairs department's training, and schools' infrastructure supports to encourage students' involvement in clubs and associations.